Improving The Quality Of Psychiatric Inpatient Discharge Certificates Through A Two Cycle Audit In A Tertiary Care Hospital In Pakistan - Bahjat Najeeb, Bahjat Najeeb; Muhammad Faisal Amir Malik, Muhammad Faisal Amir Malik; Maryam Javed, Maryam Javed; Asad Tamizuddin Nizami, Asad Tamizuddin Nizami; Azeem Rao, Azeem Rao (Resident Journal of Rawalpindi Medical University, 2024)
Objective: To assess the quality of inpatient discharge summaries according to defined standards. To design a format for discharge summary in accordance with these standards and to provide education and training to the residents about these standards. To reassess the discharge summaries after implementation and evaluate the improvement. Methods: Cycle 1: In order to improve the quality, and standardize the format of discharge summaries we formulated a set of criteria after taking input from consultants and residents. Two researchers evaluated a total of 30 discharge summaries which were randomly chosen from those issued on April May 2022. Following this a new format of discharge summary was designed and distributed. Residents were educated regarding the procedure of filling new discharge summaries.Cycle 2: Two researchers evaluated a total of 30 discharge summaries which were randomly chosen from those issues on July -August 2022. Results: In cycle 01 there was 03 (10%) mention of ICD code, gender was mentioned in 11 (36.6%), Contact Details mentioned for 02(6.67%), Inpatient Treatment 07 (23.3%) and Consultant incharge 5(16.67%). Cycle Two revealed significant improvement in most of the areas. Following the implementation there was mention of ICD code in 24 (80%), Contact Details in 20 (66.7%), Inpatient Treatment for 29 (96.7%) and Consultant-Incharge, 19(63.3%). Conclusion: Cycle 2 showed improvement in most of the areas. Factors which contributed to this would be resident education and circulation of standardized discharge forms. Keywords: Quality Improvement, Psychiatry, Inpatient, Discharge